Penyelesaian Aliran Daya 37 Bus Dengan Metode Newton Raphson (Studi Kasus Sistem Interkoneksi 150 kV Sulawesi Selatan) - Muhammad Ruswandi Djalal; Yudhi Leo Chandra; Muhammad Yusuf Yunus; Herman Nauwir (Jurnal Teknik Mesin Sinergi, 2014)
Changing in structure systems although in power plants, it must be concerned, because if one of the components out of the system, will be followed by changes in power flow and voltage profile. Study of power flow becomes very necessary to analyze power flow that occurs in electric power systems, both now and for the planning system in the future. ETAP 4.0 (Electric Transient and Analysis Program) is a software that supports the power system. Iteration method (numerical) is one of the techniques to solve power flow studies, one of the method is Newton Raphson Method. The advantage of this method is more appropriate to calculate the power flow in systems with large numbers. From the results obtained with two study cases or two conditions that is used to power flow analyze, that is : normal conditions and with the installation of shunt capacitors on the bus who suffered critical voltage, where for Buses are experiencing critical voltage at Bosowa distribution bus of 10.438 kV or 94,9% and Tanjung Bunga distribution bus at 18.818 kV or 94.1%, whereas after the addition of shunt capacitors on Bosowa distribution Bus at 10.490 kV or 95.4 % and Tanjung Bunga distribution bus at 19.209 kV or 96.0 %. Total losses amounted to 7.483 MW, where the biggest losses are on the transmission line Barru to Pangkep, that is 950.6 kW. The greatest of Active Power (P) is 62.46 MW, which flows from bus 7 Barru to bus 8 Pangkep. The greatest of Reactive Power ( Q ) is 12.55 MVAR, which flows from Bus 26 Pangkep 70 kV to Bus 27 Tonasa 70 kV. The largest voltage Buses is Bus 22 Bone about 152,315 kV or 101,54 % for normal conditions and 152,893 kV or 101.93 % after the addition of the capacitor. Thus, analysis of the results it can be concluded that after the addition of a shunt capacitor, voltage improvement made to meet the standard operating voltage, because the minimum limit of PT.PLN standard is +5% and -5%